The mediating effect of innovation on organisational culture and hotel performance: a proposed theoretical framework / Dian Aszyanti Atirah Mohd Asri - Mohd Asri, Dian Aszyanti Atirah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
This study aims to propose the theoretical framework of the mediating effect of innovation on the relationship between organisational culture and hotel performance in Malaysia. To the best of the researcher's knowledge, little is known about the role of innovation effect in the relationship between the components of organisational culture using the Competing Values Framework and hotel performance in Malaysia. Therefore, this study will determine which types of culture lead to innovation and improve performance. The use of Resource-Based View theory and its justifications among studies on the proposed framework are highlighted. A three-phased process to create this framework begins with a detailed explanation of the literature related to every component of Organisational Culture as a factor influencing hotel performance. Then, the framework inserts innovation as a strategy to improve hotel performance. Finally, innovation as a mediator between the relationship between each component of Organisational Culture and hotel performance is explained. The primary data will be gathered through a questionnaire survey sent to all the general managers of the 234 four-and five-star hotels listed on the official website of the Ministry of Tourism and Culture. The data will be analysed using SPSS and PLS-SEM. The significance of this study will support the government and the relevant organisations in developing a suitable culture related to improving and developing the hospitality industry. Furthermore, the finding will help property owners, industry players, and academicians understand the key factors that should be encouraged in order to improve organisations' performance and contribute to the literature by providing managers with practical knowledge about the significant effect of innovation on hotel performance in Malaysia.